2020
DOI: 10.21203/rs.2.22012/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extrastriatal 123I-FP-CIT SPECT impairment in Parkinson’s disease – the PPMI cohort

Abstract: Background: Neuropathological data and nuclear medicine imaging show extensive serotonergic impairment in Parkinson’s disease (PD). We aimed at undertaking a case-controlled analysis of 123I-FP-CIT SPECT images to measure extrastriatal serotonergic transporters (SERT) in PD using the Parkinson’s Progression Markers Initiative (PPMI) cohort. Methods: We included all PD (n=154) and Control subjects (n=62) with available 123I-FP-CIT SPECT imaging and high-resolution T1-weighted MRI for coregistration (PD: mean ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…11 C‐3‐amino‐4‐(2‐dimethylaminomethyl‐phenylsulfanyl)benzonitrile (DASB), have shown reduced binding in caudate nucleus, thalamus and anterior cingulate regions (Politis et al, 2010). Using 123 I‐FP‐CIT, recent studies have confirmed these findings, showing a decreased binding in pallidum, cingulate areas, amygdala and insula in PD and atypical parkinsonisms (Joling et al, 2017; Nicastro et al, 2020; Nicastro et al, 2020; Pilotto et al, 2019; Premi et al, 2017) (Figure 3).…”
Section: Degenerative Parkinsonisms and Their Dopaminergic Pet/spect ...mentioning
confidence: 65%
“…11 C‐3‐amino‐4‐(2‐dimethylaminomethyl‐phenylsulfanyl)benzonitrile (DASB), have shown reduced binding in caudate nucleus, thalamus and anterior cingulate regions (Politis et al, 2010). Using 123 I‐FP‐CIT, recent studies have confirmed these findings, showing a decreased binding in pallidum, cingulate areas, amygdala and insula in PD and atypical parkinsonisms (Joling et al, 2017; Nicastro et al, 2020; Nicastro et al, 2020; Pilotto et al, 2019; Premi et al, 2017) (Figure 3).…”
Section: Degenerative Parkinsonisms and Their Dopaminergic Pet/spect ...mentioning
confidence: 65%